A Latin Lover in Ancient Rome : Readings in Propertius and his Genre - Johnson, W. R. (Walter Ralph), 1933-; Project Muse. (Columbus : Ohio State University Press, 2009)
Over the centuries, Latin love elegy has inspired love poetry in the West from Petrarch to Pound. A Latin Lover in Ancient Rome: Readings in Propertius and His Genre offers a critical reevaluation of the Latin elegiac poet Propertius, situating him within the social and political milieu of first-century BCE Rome. W. R. Johnson's study is centered on close readings of the poems in Propertius' four books that emphasize both his celebration of erotic freedom as a manifestation of the sovereignty of the individual and his insistence on the value of this freedom, especially when it is threatened by autocratic ideology. Many recent titles on Propertius have tended to minimize or ignore this aspect of the poet's work, concentrating instead on neo-formalism or Lacanian psychology. Johnson restores Propertius' erotic creed and his politics to the core of his poetics and his career. He offers a vivid picture of the sociopolitical and erotic world of the late Roman Republic and the early years of the Empire which hatched Latin love elegy and allowed it to flourish. This study aims to redirect attention to the pleasures and energies Propertius provides that later generations of poets and readers discovered in and through him.
The d/evolution of love -- Aeneas in love -- Two portraits of the lady -- Propertius and the poetics of disgregation -- Whatever happened to Latin love elegy?
Description based on print version record.
Keywords: Propertius, Sextus; Propertius, Sextus -- Criticism and interpretation; Propertius, Sextus -- Criticism and interpretation; Love poetry, Latin; Elegiac poetry, Latin; Poesie d'amour latine -- Histoire et critique; Poesie elegiaque latine -- Histoire et critique; Elegiac poetry, Latin -- History and criticism; Love poetry, Latin -- History and criticism; Criticism, interpretation, etc; Electronic books